SELinux cookbook : over 70 hands-on recipes to develop fully functional policies to confine your applications and users using SELinux /: over 70 hands-on recipes to develop fully functional policies to confine your applications and users using SELinux. (2014) - Vermeulen, Sven
No abstract available